The second representative of the genus Polididus (Hemiptera: Heteroptera: Reduviidae) in Southeast Asia, with partial redescription of P. armatissimus - Ishikawa, Tadashi; Sumiartha, Ketut; Okajima, Shûji (Zootaxa, 2008)
A new species of the harpactorine genus Polididus is described from Flores, Indonesia, on the basis of female specimens under the name P. dimorphopterus sp. nov. as the second representative of the genus in Southeast Asia. This species is unique among the congeners in showing wing dimorphism and is easily recognized by the pronotum dark brown to blackish with a pair of brownish yellow longitudinal stripes, setiferous spines on the pronotal humeri, scutellum and laterotergites IV to VII blackish in the basal half and brownish yellow in the apical half, the femur of each leg blackish in the apical fifth, the mesoand metatibiae lacking setiferous spine, the metatibia with a blackish narrow annulation subbasally. Polididus armatissimus is recorded from Bali for the first time, with descriptions and illustrations of the male and female genitalia.